Effect of intracranial venous collaterals on neurological outcomes in cerebral venous thrombosis. (August 2022) - Zhao, Yanying; Su, Xudong; Liu, Zengpin; Zhou, Cunhe; Yu, Jianghua; Wang, Xiaopeng; Zhou, Lixia; Shi, Zhaoxia; Liu, Lin; Lu, Honglin; Zhao, Pandi; Li, Zhongzhong; et al.
Highlights: Prognostic factors for cerebral venous thrombosis (CVT) are under-reported. Male sex and age ≤ 35 years are associated with good collateral formation. Male sex, subacute onset, and good collaterals are associated with good outcomes. Venous collaterals are associated with early (not late) recanalization. Venous collateral formation should be evaluated in patients with CVT. Abstract: This study identifies predictors of favourable intracranial venous collaterals and the effect of intracranial venous collaterals on outcomes and recanalization in patients with cerebral venous thrombosis (CVT). Data of 61 patients with CVT were retrospectively reviewed. Venous collateralization was defined as expanded cortical vein formation through different drainage pathways. Recanalization grades were classified into complete or partial recanalization based on images obtained during hospitalisation and follow-up. Independent predictors of collateral formation and poor prognosis were investigated via univariate and binary logistic regression analyses. The effects of different intracranial venous collaterals on recanalization in patients with CVT were assessed. A risk prediction nomogram for prognosis was constructed. Age ≤ 35 years (odds ratio (OR) = 7.067; 95% confidence interval (CI) = 1.776–28.277; P = 0.006) and male sex (OR = 5.490; 95% CI = 1.205–25.004; P = 0.028) were independent predictors of favourable venous collaterals. Venous collaterals were associated with early recanalization ( P = 0.017) and not with long-term recanalization ( P = 0.252). Male sex (OR = 0.047; 95% CI = 0.003–0.651; P = 0.023), subacute onset (OR = 0.026; 95% CI = 0.002–0.367; P = 0.007), and good collateral grade (OR = 0.168; 95% CI = 0.029–0.985; P = 0.048) were independent factors of favourable neurological outcomes at discharge. Haemorrhage on computed tomography at admission (OR = 10.868; 95% CI = 2.082–56.733; P = 0.005) was inversely correlated with prognosis. These findings suggested that male patients under 35 years of age are more likely to have favourable venous collaterals and good outcomes. Venous collaterals are significantly associated with early recanalization. These findings highlight the importance of venous collateral evaluation in patients with CVT.